Transitions to democracy: what theory to grasp complexity? - Morlino, Leonardo A. (Historein, 2015)
When analysing transitions towards democracy during the last three decades of the 20th century and the first decade of the 21st century, it is readily apparent that the variety of empirical processes is so wide that achieving meaningful theoretical results is extremely difficult, as the existing literature on the topic shows explicitly. This paper addresses the key theoretical questions that need to be dealt with by the empirical analysis of the transitional process. Are there key, recurring actors and factors that we should take into account when analysing all cases in depth? Why is a focus on installation (not only on transition) salient? Are there recurring patterns of successful transitions? Are there key recurring mechanisms that critically explain successful transitions? And are there obstacles that make it impossible to achieve a successful transition and doom such a process to failure? On the basis of existing knowledge in the subfield, an attempt is made to reply to these questions, and in this way to single out the main theoretical results achieved in the field.